2006
DOI: 10.1002/ffj.1608
|View full text |Cite
|
Sign up to set email alerts
|

Studies on essential oils, Part 41. Chemical composition, antifungal, antioxidant and sprout suppressant activities of coriander (Coriandrum sativum) essential oil and its oleoresin

Abstract: Gas chromatography-mass spectrometry (GC-MS) analysis of the seed oil of coriander (Coriandrum sativum) showed the presence of 52 components, accounting for 98.45% of the total oil. The major components were linalool (75.30%), geranyl acetate (8.12%) and α α α α α-pinene (4.09%). Its oleoresin showed the presence of 28 components. Oleic acid (36.52%), linoleic acid (33.2%) and palmitic acid (11.05%) were the major components. The antifungal activities of coriander oil and its oleoresin against eight fungi were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 38 publications
1
42
0
2
Order By: Relevance
“…In our opinion major components of thyme (thymol (33.14%), carvacrol (19.59%), linalool (16.00%) and -cymene (10.30%)), summer savory (carvacrol (24.50%), thymol (23.12%) andterpinene (20.72%)) and clove oil (eugenol (63.37%), -caryophyllene (15.94%) and eugeyl acetate (13.14%)) have key roles in their antifungal activities. Antifungal activities of these compounds have been reported by others (Burt, 2004;Nguefack, Letha, Amvam Zollob, & Mathura, 2004;Singh, Maurya, Lampasona, & Catalan, 2006). However, the mechanisms of action of these compounds have not been completely elucidated.…”
Section: Antifungal Activity In Vivomentioning
confidence: 93%
“…In our opinion major components of thyme (thymol (33.14%), carvacrol (19.59%), linalool (16.00%) and -cymene (10.30%)), summer savory (carvacrol (24.50%), thymol (23.12%) andterpinene (20.72%)) and clove oil (eugenol (63.37%), -caryophyllene (15.94%) and eugeyl acetate (13.14%)) have key roles in their antifungal activities. Antifungal activities of these compounds have been reported by others (Burt, 2004;Nguefack, Letha, Amvam Zollob, & Mathura, 2004;Singh, Maurya, Lampasona, & Catalan, 2006). However, the mechanisms of action of these compounds have not been completely elucidated.…”
Section: Antifungal Activity In Vivomentioning
confidence: 93%
“…Different studies have proven that coriander extracts and essential oil exhibit antioxidant activities (Guerra, Melo, & Filho, 2005;Singh, Maurya, de Lampasona, & Catalan, 2006). Wangensteen, Samuelsen, and Malterud (2004) demonstrated that coriander leaves showed stronger antioxidant activity, tested by DPPH, the inhibition of 15-lipoxygenase and inhibition of Fe 2+ -induced porcine brain phospholipid peroxidation, than the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the antifungal activity of EO against A. flavus and A. fumigaths [21]. Some authors also described the antifungal activity of C. sativum EO against A. niger [22], A. terreus, A. flavus, Trichothecrum roseum, Fusarium graminearum, Fusarium oxysporum, Fusarium moniliforme and Curvularia palliscens [23]. Antifungal activity of the CEO was tested on Penicillium lilacinum and A. niger, MIC was determined 2.5 and 2.3 mg/mL, respectively [24].…”
Section: Antifungal Activity In Vitromentioning
confidence: 98%